ASUHAN KEPERAWATAN PADA KLIEN DENGAN KISTA ENDOMETRIOSIS MENGGUNAKAN PENDEKATAN TEORI COMFORT DAN LOSS & GRIEF - Marlinda Marlinda; Yati Afiyati; Tri Budiati (LPPM Sikes Panca Bhakti Bandar Lampung, 2018)
Endometriosis cysts or chocolate cyst is a benign tumor that often occurs in the female reproductive system at this time. Women with this problem would be impaired on a woman's quality of life both physically, psychospiritual, environment, and socio-cultural. Another risk is the incidence of malignancies of the reproductive system. The purpose of this report is to provide an overview of the implementation of the practice peneliticy specialist nurses are managing client cases cysts of endometriosis with a case study approach to apply the theory of comfort and loss and grief. Care given to overcome the discomfort experienced by clients both physically, psychospiritual, environmental and socio-cultural, management during surgery is done on the client. Selection of comfort nursing theory concepts elaborated the theory of loss and grief can be complementary so that the care provided can be maximized.